Reversible computation : Third international workshop, RC 2011, Gent, Belgium, July 4-5, 2011. Revised Papers - Wille, Robert; Vos, Alexis (Lecture Notes in Computer Science, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Reversible Computation, RC 2011, held in Gent, Belgium, in July 2011. The 10 revised full papers presented were carefully reviewed and selected from 25 initial submissions for inclusion in the book. The papers are devoted to all aspects of reversible computation, ranging from theoretical and experimental aspects to various applications. Topics addressed are: functional language for reversible computations, logic design, reversible circuits designed by a software toolkit called RevKit, application of reversible computation to the domain of quantum circuits, and physical realizations of reversible circuits in CMOS technologies.